2020
DOI: 10.1016/j.omto.2020.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced DNMT3B Promotes Radioresistance in Nasopharyngeal Carcinoma through Methylation of p53 and p21

Abstract: Radiotherapy with or without concurrent chemotherapy is the standard treatment for nasopharyngeal carcinoma (NPC) patients, whose efficacy is limited partly by intrinsic and acquired radioresistance. DNA methyltransferase 3B (DNMT3B) has been reported to participate in tumorigenesis via DNA methylation, but its role in mediating progression and radioresistance of NPC remains unclear. Therefore, we conducted the following studies to explore the relationship between DNMT3B and NPC. Here, we found that DNMT3B was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…This raises the question of whether EVs can shield the target tumors from DNMT3B inhibitors. Additionally, DNMT3B has been reported to contribute in chemotherapy resistance [ 37 ] and promotes radio-resistance in nasopharyngeal carcinoma [ 38 ]. DNMT3B in BAL EVs mirrors the expression in lung tumor tissue, and this might give a novel opportunity to use it as a marker for chemotherapy and radio-resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question of whether EVs can shield the target tumors from DNMT3B inhibitors. Additionally, DNMT3B has been reported to contribute in chemotherapy resistance [ 37 ] and promotes radio-resistance in nasopharyngeal carcinoma [ 38 ]. DNMT3B in BAL EVs mirrors the expression in lung tumor tissue, and this might give a novel opportunity to use it as a marker for chemotherapy and radio-resistance.…”
Section: Discussionmentioning
confidence: 99%
“…miR-221-3p and miR-222-3p reduce radiosensitivity in thyroid cancer cells. It was previously reported that EMT was associated with decreased cancer sensitivity to radiation therapy (22)(23)(24)(25). Therefore, a colony formation assay was used to determine the role of miR-221-3p and miR-222-3p in radiosensitivity.…”
Section: Mir-221-3p and Mir-222-3p Regulate The Expression Levels Of P-stat3 Emt-related Markers And Nis In Thyroid Cancer Cellsmentioning
confidence: 99%
“…The Ras signaling pathway is closely related to the occurrence and progression of most human tumors [ 64 67 ]. The activation of RAS-RAF-MEK-MAPK in gene transcription regulation can promote proliferation, migration, and angiogenesis of cancer cells [ 68 70 ]. RAS-PI3K interaction is an important signaling node and potential therapeutic target in EGFR-mutant lung cancer [ 71 73 ].…”
Section: Discussionmentioning
confidence: 99%